Municipal asset operations and maintenance performance in metropolitan and rural municipalities in Gauteng Province and Vhembe District Local Municipalities, South Africa. Issue 1 (1st January 2021) - Bikam, Peter; Chakwizira, James
Abstract: Municipal infrastructure asset operations and maintenance are critical for municipalities to provide basic services to communities in South Africa. The paper discusses the performance of municipal assets using Key Informants and literature review based on three metropolitan areas in Gauteng province and four rural municipalities in Limpopo province of South Africa focusing on asset operations and maintenance. Municipal assets in South Africa are saddled with poor performance because the infrastructure is aging in a context of rapid urbanisation and population growth and this impacts on the level of service delivery to the communities. The method used to analyse and unpack the findings were obtained from the review of literature and information obtained from Key Informants. The major official documents used includes the Sector Plans, Spatial Developments Frameworks, Integrated Development Plans as well as the review of books and journals on the general performance of the metros and rural municipalities with respect to municipal asset operations and maintenance. The information obtained from the Key Informants was used to refute or confirm the notion from the literature reviewed that inadequate operations and maintenance of municipal assets contribute to under performance in the provision of basic service delivery to the communities. The study shows that insufficient funding and low revenue base of the municipalities impacts on the renewal of municipal assets and provision of basic services to the communities in both metros and rural municipalities. The study recommends appropriate systems and asset management practices that can be put in place to improve on the under-performance of operations and maintenance.